The Effect of Marketing Mix on Customer Satisfaction at Sinar Terang Elektrik Stores in Medan City - Rini Anggraini; Sugih Arto Pujangkoro; Iskandarini (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to determine the effect of product, price, promotion, and location on consumer satisfaction. All data in this study were obtained from research using questionnaires in Medan. The analysis technique in this study used multiple regression analysis using the Statistical Package for the Social Sciences (SPSS). The population of this study were consumers of Sinar Terang Elektrik Stores, with a sample of 96 respondents based on random sampling. The results showed that the influence of the marketing mix simultaneously and partially had a significant effect on customer satisfaction. However, only product and price significantly affect customer satisfaction, while promotion and location do not.